THE MEANING OF THE RECEPTION OF THE LETTERS MUQAṬṬA’AH IN ḤIZB AL-NAṢR BY ABÛ AL-ḤASAN AL-SHÂDHILÎ - Dhur Anni; Lukman Hakim (UIN Sunan Kalijaga Yogyakarta, 2020)
The meaning of the letters muqaṭṭa’ah at the beginning of several surahs in the Qur'an is still considered mysterious. Many narrations show the search for their meaning by relating to the virtue and purpose of using these letters. The virtue explained by the Prophet and his companions made these letters used in their literal form, such as Abû al-Ḥasan al-Shâdhilî, who used them as part of the dhikr in the Ḥizb al-Naṣr. This study aims to find al-Shâdhilî’s acceptance in his collection of dhikr and prayers. To achieve this purpose, this study uses qualitative methods with data analysis techniques using diachronic approaches and syntagmatic analysis introduced by Ferdinand de Saussure. This study found a shift in meaning and acceptance of the letters muqaṭṭa’ah carried out by al-Shâdhilî. Al-Shâdhilî uses the letters muqaṭṭa’ah as part of the intermediary to make prayer more acceptable. This is based on the view that these letters contain the names of the Great God. Al-Shâdhilî’s shift in acceptance of the letters muqaṭṭa’ah in the Arab community has a significant difference with the acceptance of the Arab community for the Qur'an, which tends to be informative, so acceptance is done by exegesis, whereas al-Shâdhilî accepted the letters functionally in the performative realm.